Sustained censorship in IQ (2026-04) (Iraq) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Iraq. Data sourced from OONI.
Censorship Incident ID: IQ-2026-0198. Severity: critical. Confidence: 85%